Analisis Minat Peserta Didik SMP dalam Pembelajaran Permainan Bola Tangan Berdasarkan Faktor Intrinsik dan Ekstrinsik - Isnaini, Nur Hasan; Ngatman, Ngatman; Susanto, Ermawan (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Handball learning at SMP Ma’arif Borobudur has not been optimally implemented. This study aimed to identify eighth-grade students’ interest in learning handball based on intrinsic and extrinsic factors. The study employed a descriptive quantitative design using a survey method. The population and sample consisted of all eighth-grade students of SMP Ma’arif Borobudur in the 2023/2024 academic year, totaling 51 students, selected through total sampling. The research instrument was a closed-ended questionnaire consisting of 30 items using a Likert scale. Data were analyzed using descriptive statistics, including mean, standard deviation, frequency, and percentage. The results showed that students’ overall interest was in the moderate category, with a mean score of 81.24. The intrinsic factor was also in the moderate category, with a mean score of 60.22, while the extrinsic factor was in the moderate category, with a mean score of 21.02. In conclusion, students’ interest in handball learning is adequate but needs improvement through game modification, creative teaching strategies, and better school facility support.